Sedimentology of coexisting travertine and tufa deposits in a mounded geothermal spring carbonate system, Obruktepe, Turkey. Issue 4 (2nd March 2017) - Lopez, Benjamin; Camoin, Gilbert; Özkul, Mehmet; Swennen, Rudy; Virgone, Aurélien
Abstract: The recent discoveries of deeply buried Cretaceous reservoir bodies in the Atlantic Ocean revealed that relationships between the distribution of spring carbonate deposits and faults are poorly understood. The well‐exposed Quaternary deposits at Obruktepe (Denizli Basin, Turkey) provide an opportunity to reconstruct the three‐dimensional sedimentary architecture of such a system. Integration of sedimentological, lithofacies and geochemical analyses reveals complexity in the lateral relationships between sedimentary environments, faults and geothermal spring carbonates. Five environmental systems are distinguished based on the lithofacies analysis: (i) vent; (ii) smooth slope; (iii) travertine‐terrace; (iv) tufa‐barrage; and (v) flood systems. Encrusting, baffling and settling sedimentary processes are reflected in data acquired at several scales, from lithofacies observations to the morphology and arrangement of geobodies, together with microfabrics and stable carbon and oxygen isotope data. Mean values of +4·9‰ δ 13 C and −8·74‰ δ 18 O Vienna PeeDee Belemnite reflect geothermal circulation of springwaters. The environmental distribution and lithofacies indicate a lateral continuum between travertine and tufa deposits within this hot spring system. This finding supports two depositional models in which water flow variation is the main control on both CaCO3 precipitation and the resulting formation of travertine and tufa. The proposed models address the factors responsible for the development of these complex mound‐shaped carbonate spring deposits, and how they are related to fluid circulation at depth and in association with faults.